1983
DOI: 10.1210/endo-113-6-2216
|View full text |Cite
|
Sign up to set email alerts
|

Androstenedione, Testosterone, and Estradiol Concentrations in Fetal and Maternal Plasma in Late Pregnancy in the Sheep*

Abstract: Fetal and maternal plasma concentrations of androstenedione, testosterone, and estradiol were measured in chronically catheterized pregnant sheep during late gestation, spontaneous term delivery, and premature delivery induced by the infusion of low doses of synthetic ACTH-(1-24) (ACTH) to the fetus at 120-130 days gestation. RIAs employing two different antisera directed at different sites of each molecule were used in combination with Celite column chromatography to ensure the specificity of the hormone meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 10 publications
2
15
1
Order By: Relevance
“…However, none of these studies reported the estradiol concentration achieved in maternal or fetal plasma at the dose of estradiol used in their studies. In a pilot study, we found that infusion of estradiol at a rate of 2 mg/d only raised fetal or maternal plasma estradiol up to 20 -25 pg/ml (data not shown), well below the level observed in maternal plasma at spontaneous labor (10,24,25). At the dosage used in the present study, we were able to produce maternal plasma estradiol concentrations of about 350 pg/ml (Fig.…”
Section: Discussioncontrasting
confidence: 42%
“…However, none of these studies reported the estradiol concentration achieved in maternal or fetal plasma at the dose of estradiol used in their studies. In a pilot study, we found that infusion of estradiol at a rate of 2 mg/d only raised fetal or maternal plasma estradiol up to 20 -25 pg/ml (data not shown), well below the level observed in maternal plasma at spontaneous labor (10,24,25). At the dosage used in the present study, we were able to produce maternal plasma estradiol concentrations of about 350 pg/ml (Fig.…”
Section: Discussioncontrasting
confidence: 42%
“…Conversely estradiol concentrations are similar between male and female rat fetuses (239), and exceed the maternal concentration (146,239). In fetal lambs, testosterone and estradiol exceeded the maternal concentration at all time points (117,650,757).…”
Section: Sex Steroidsmentioning
confidence: 86%
“…However, the percentage of LH cells remained stable at that time, suggesting that a "dilution" of gonadotropes in other pituitary cells is not the main factor involved in this decrease. At the same period, there is a decline in plasma LH and FSH levels [28], most probably due to the rise in fetoplacental sex steroids and perhaps to an anti-gonadotropic action of PRL [34][35][36]. Since these hormones are able to inhibit directly or indirectly [37][38][39][40] the synthesis of LH and/or FSH, the decrease in the percentage of FSH cells observed at this moment could also be due to cells' becoming undetectable because of the small amounts of gonadotrope hormones they contain.…”
Section: Discussionmentioning
confidence: 99%